Crafting and Executing Strategy - Gamble John E; Peteraf Margaret A; Strickland A.J; Thompson Arthur (Mcgraw Hill Irwin, 2012)
This book empowers students to design a strategy aimed at winning a competitive advantage for their company in head - to - head competition against companies run by their classmates. Concepts and Techniques for Crafting and Executing Therapy, What is Strategy and Why is it Important?, Charting a Company's Direction: Vision and Mission and Objectives and Strategy, Evaluating a Company's External Environment, Evaluating a Company's Resources and Capabilities and Competitiveness, The Five Generic Competitive Strategies: Which One to Employ?, Strengthening a Company's Competitive Position: Strategic Moves and Timing and Scope of Operations, Strategies for Competing in International Markets, Corporate Strategy: Diversification and the Multibusiness Company, Ethics and Corporate Social Responsibility and Environmental Sustainability and Strategy, Building an Organization Capable of Good Strategy Execution: People and Capabilities and Structure, Managing Internal Operations: Actions that Promote Good Strategy Execution, Corporate Culture and Leadership: Keys to Good Strategy Execution, Indexes.